Health commitment to protection from Coronavirus and its relationship to cognitive flexibility among a sample of adults and elderly Kuwaiti society - AL-Ajmi, Rashed Manea Rashed; Al-Otaib, Abdullah Hezam Ali (Journal of Educational and Psychological Sciences, 2021)
This study aims to identify the level of both Health Commitment and Cognitive flexibility among a sample of adults and elderly Kuwaiti society, and to reveal the differences in the level of both health commitment and cognitive flexibility according to the variables (Gender- Nationality- Age -Educational level), additionally to identify the relationship between Healthy commitment and between cognitive flexibility.To achieve the objectives of the study, the study prepared two tools: the scale of health commitment, and the scale of cognitive flexibility, and extracted the indications of their validity and stability. The sample of the study consisted of (198) individuals from the Kuwaiti society.The results of the study showed that the level of health commitment among the Kuwaiti society members was high, and there were no significant statistical differences in the level of health commitment according to the variables of sex, nationality, and educational level, while there were significant statistical differences in the level of health commitment according to the variable of age and in favor of the age group (40-50) years old.The results also indicated that the level of cognitive flexibility among members of Kuwaiti society was high, and there were statistically significant differences in the level of cognitive flexibility, according to the gender variable and in favor of females, according to the age variable and in favor of the age group (40-49) years, while there were no significant statistical differences. Significant level of cognitive flexibility according to the variables of nationality and educational level. The results also indicated a high and positive correlation between healthy adherence and cognitive flexibility.
Keywords: Health Commitment; Emerging Coronavirus; Cognitive Flexibility; Kuwaiti Society